Differential Characteristics of the Delayed and Underdeveloped Speech and Language Development in Pre-school Children - Kantanavičiūtė-Petrūžė, Rita; Ladukienė, Auksė (Special Education, 2024)
The article reveals the theoretical differential aspects of delayed and underdeveloped speech and language development, analyses opinions and experiences of speech and language therapists by differentiating the disorders of delayed and underdeveloped speech and language development, identifying main differential characteristics of these disorders. The methodological approach of quantitative research and a written survey as a quantitative method for the research data collection were chosen for the research. Speech and language therapists of Lithuania who had practical experience in providing assistance to preschool children with delayed and underdeveloped speech and language development participated in the study. The study revealed main differential characteristics of delayed and underdeveloped speech and language development. The main differential differences of delayed and underdeveloped speech and language development are observed at the phonetic, phonological, lexical and semantic, morphological and syntactic levels.